Концептуальный подход к моделированию инновационного развития в сфере информационных технологий фирмы - Бажан, Л.И.; Безуглая, Е.А. (Управляющие системы и машины, 2015)
Исследуются возможности использования инноваций в сфере информационных технологий, способствующих развитию хозяйствующих субъектов, повышению уровня их конкурентоспособности, умение разрабатывать стратегию поиска решения практических задач, прогнозировать и анализировать результаты принятых решений на основе моделирования информационных процессов, явлений, их взаимосвязей. Исследуются внешние и внутренние факторы инновационного развития в сфере информационных технологий коммерческой фирмы, что позволяет сформулировать концептуальный подход к моделированию инновационного развития. Досліджено можливості використання інновацій у сфері інформаційних технологій, що сприяють розвитку господарюючих суб'єктів, підвищенню рівня їх конкурентоспроможності, вміння розробляти стратегію пошуку вирішення практичних завдань, прогнозувати і аналізувати результати прийнятих рішень на основі моделювання інформаційних процесів, явищ, їх взаємозв'язків. Досліджено зовнішні та внутрішні чинники інноваційного розвитку у сфері інформаційних технологій комерційної фірми, що дозволяє сформулювати концептуальний підхід до моделювання інноваційного розвитку. An important characteristic of the processes occurring in society is its global informatization. The main objective of the
information process of modern society is the development of the theory and practice of using the modern information and
communication technologies to facilitate the development of economic subjects, to improve their competitiveness and ability
to develop a search strategy for solving practical problems, to forecast and analyze results of the decisions made on the basis
of the modeling of information processes, phenomena and relationships between them.
The development of new technical means, discovery of the new concepts and means of data organization, transfer, storage and
processing results in a continuous development and improvement of information technologies. Nowadays, information technologies
are the main driving force of market economy, enabling to implement complex manufacturing solutions, control the transparency of
financial and commodity flows, manage personnel costs and optimize relationships with suppliers. Establishment of new information and communication technologies, its development and use in business and commercial activity is continuous and natural process that has a great influence on the processes of globalization, on the one hand, and formation of stable structures of economic entities under non-equilibrium economy, on the other hand.
For this purpose, issues of using of innovations in information technology are investigated that are contributing to development
of economic agents, improve their competitiveness and ability to develop a search strategy for solving practical problems, predict
and analyze outcomes of decisions made on basis of modeling of information processes, phenomena and its interrelations.
External and internal factors of innovative development are studied in the field of information technology of commercial
company that allows to formulate a conceptual approach to the modeling of innovative development.
External factors include general economic, legal and infrastructure ones. Internal factors are also infrastructure and management ones. Assignment of infrastructural factors (level of development of information and communication technologies,
size and growth of Internet audience, level of intellectual potential in the development of computer technology) to both external and internal factors confirm a hypothesis of influence of globalization processes on the sustainability of the company, as
an economic entity, depending of the level of development of information and communication sphere.
Necessity for innovative transformations is caused by the disturbance of the equilibrium state of a commercial firm, which
occurs as a result of increasing information flows that accompany material and financial ones.
A general assessment of the level of innovative development of a commercial firm is proposed, depending on influence of
external and internal environment factors, as well as schema of strategy elaboration for its innovative development.